2009
DOI: 10.1111/j.1365-2249.2009.03915.x
|View full text |Cite
|
Sign up to set email alerts
|

Human gingival fibroblasts express functional chemokine receptor CXCR6

Abstract: SummaryWe have reported that CXCL16, a recently discovered transmembrane chemokine, is expressed in human gingival fibroblasts (HGF). However, it is not known whether HGF express CXCR6, the receptor for CXCL16, or CXCL16 affects HGF biology. We have shown that HGF expressed CXCR6 by reverse transcription-polymerase chain reaction and flow cytometric analysis. Moreover, we elucidated that tumour necrosis factor (TNF)-a and cytosine-guanine dinucleotide (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Also in line with us CXCR6 expression was reported as absent on gingiva fibroblasts and in gingiva tissue derived from clinically healthy patients (Hosokawa, Hosokawa, Ozaki, Nakae, & Matsuo, ). However, in a later study the same authors did detect CXCR6 expression and found that its ligand CXCL16 could induce gingiva fibroblast proliferation (Hosokawa, Hosokawa, Ozaki, Nakae, & Matsuo, ). These contradictory results may possibly be explained by different culture conditions and the inflammatory state of the gingiva tissue in the different studies.…”
Section: Discussionmentioning
confidence: 97%
“…Also in line with us CXCR6 expression was reported as absent on gingiva fibroblasts and in gingiva tissue derived from clinically healthy patients (Hosokawa, Hosokawa, Ozaki, Nakae, & Matsuo, ). However, in a later study the same authors did detect CXCR6 expression and found that its ligand CXCL16 could induce gingiva fibroblast proliferation (Hosokawa, Hosokawa, Ozaki, Nakae, & Matsuo, ). These contradictory results may possibly be explained by different culture conditions and the inflammatory state of the gingiva tissue in the different studies.…”
Section: Discussionmentioning
confidence: 97%
“…Further, TNF‐ α and IFN‐ γ enhanced ICAM‐1 and vascular cell adhesion molecule 1 expression in HGFs, and IL‐1 β upregulated ICAM‐1 expression (Hosokawa et al 2006). IL‐1 β , TNF‐ α and IFN‐ γ also increased expression of CXCL16 in HGFs with synergism between IFN‐ γ and IL‐1 β (Hosokawa et al 2007), and HGFs also expressed CXCR6, the receptor for CXCL16 (Hosokawa et al 2009b). A combination of TNF‐ α and IL‐4/IL‐13 increased CCL17 expression (Hosokawa et al 2008).…”
Section: Part 3: Cytokine Interactions and Immune Regulation In Periomentioning
confidence: 99%
“…6A). These signaling pathways, including p38 and ERK, are also involved in the expression of MMP-9 (34,43), CXCR4 and CXCR6 (44,45). In addition, previous studies have revealed that F-actin re-arrangement is also regulated by the p38 or ERK signaling pathways (46,47).…”
Section: Discussionmentioning
confidence: 98%